Pengaruh Kompensasi Finansial Dan Non Finansial Terhadap Kinerja Karyawan Dengan Budaya Organisasi Sebagai Variabel Moderasi - Yunita Christy; Sinta Setiana; Chandra Wijaya (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
Compensation is one of the existed factors encountered by every organization. Compensation is aimed to satisfy employees both financially and non-financially. Meanwhile, organization culture is a tool that shapes the habits and characters of employees within the organization. It is said that a good compensation system supported by exemplary good organization cultures is expected to boost the motivation of employees and to cultivate good personality among them which later can influence the organization's performance. Based on these facts, this study tested three hypotheses using Moderating Regression Analysis (MRA) by collecting data from 50 employees at CV ‘X’ which focuses its core business in motorcycle spare part distribution. Regarding the data collected, the findings showed that both financial and non-financial compensation influence the performance of the employees. However, the organization culture cannot moderate the relation between financial and non-financial compensation and organization performance. Therefore, it can be concluded that the existence of organizational culture cannot add more value to both financial and non-financial compensation in terms of influencing the performance of the employees within the current company.  Kata kunci                    :Kompensasi Finansial, Kompensasi Non Finansial, Budaya Organisasi, Kinerja